Smart Device for the Determination of Heart Rate Variability in Real Time. (27th November 2017) - Naranjo-Hernández, David; Roa, Laura M.; Reina-Tosina, Javier; Barbarov-Rostan, Gerardo; Galdámez-Cruz, Omar
Abstract : This work presents a first approach to the design, development, and implementation of a smart device for the real-time measurement and detection of alterations in heart rate variability (HRV). The smart device follows a modular design scheme, which consists of an electrocardiogram (ECG) signal acquisition module, a processing module and a wireless communications module. From five-minute ECG signals, the processing module algorithms perform a spectral estimation of the HRV. The experimental results demonstrate the viability of the smart device and the proposed processing algorithms.